Thai bureaucracy system: Thai bureaucracy, Thai administration principle, absolute monarchy, democracy - Phuengpha, Noppawan (JAMAK: Jurnal Administrasi Manajemen dan Kepemimpinan, 2020)
Administration of each country has long history and different influence factors. The situation of country is one of factor that leads changing and development of bureaucracy. In Thailand, the bureaucracy system appears more than one thousand year ago. The Thai bureaucracy can divide to two periods; absolute monarchy and democracy. In absolute monarchy period, the king is the highest administrator. The king can provide the rules, regulations, and laws. In term of democracy period, according to all the constitutions of the Kingdoms of Thailand; chapter one section two; Thailand adopts a democratic regime of government with the King as Head of State. Section three; The sovereign power belongs to the Thai people. The King as Head of State shall exercise such power through the National Assembly, the Council of Ministers and the Courts in accordance with the provisions of this Constitution. The performance of duties of the National Assembly, the Council of Ministers, the Courts, the Constitutional organizations and State agencies shall be in accordance with the rule of laws. Base on the constitution, the head of administration of Thailand is the Prime Minister that come from choose one of member of the house of representative. The member of house of representative come from election.In the paper, the writer does not explain the Prime Minister, member of the house of representative and senator. The purpose of this paper is to present an integrative review of the literature to explore the Thai bureaucracy system by describing Thai Bureaucracy with the bureaucratic system of Weber. The finding of the paper shows Thai bureaucracy includes the permanent structure as central level, provincial level, and local government. The three administration principles structure run as the parallel structure that include centralization, deconcentration and decentralization. In difference King era, the structure of Thai bureaucracy system was adjusted by establishing of new bureaus or sometimes, some bureau was merged, however, adjusting structure cannot confirm that there are no duplication jobs.